New Multitarget Approaches in the War Against Glioblastoma: A Mini-Perspective - Sestito, Simona; Runfola, Massimiliano; Tonelli, Marco; Chiellini, Grazia; Rapposelli, Simona (Frontiers in Pharmacology, 2018)
Glioblastoma Multiforme (GBM) is the most common tumor of the central nervous system (CNS), and the deadliest form of brain cancer. The rapid progression, the anatomic location in the brain and a deficient knowledge of the pathophysiology, often limit the effectiveness of therapeutic interventions. Current pillars of GBM therapies include surgical resection, radiotherapy and chemotherapy, but the low survival rate and the short life expectation following these treatments strongly suggest the urgency to identify innovative and more effective therapeutic tools. Frequently, patients subjected to a mono-target therapy, such as Temozolomide, develop drug resistance and undergo relapse, indicating that targeting a single cellular node is not sufficient for eradication of this disease. In this context, a multi-targeted therapeutic strategy aimed to develop compounds able to inhibit more than one specific molecular target, offers a promising alternative and has already been well integrated into drug discovery campaigns, including the field of anticancer drugs. In this miniperspective, we will discuss the recent progress in the treatment of GBM focusing on innovative and effective preclinical strategies which are based on the multi-targeted approach.